STRATEGI PENGELOLAAN APBG DALAM MENCEGAH WABAH COVID-19 DI GAMPONG KRUENG DHOUE KECAMATAN PIDIE KABUPATEN PIDIE - Rozailli Rozailli; Zulfikar Zulfikar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
Based on domestic law number 3 of 2020 reguarding the prevention of corona virus disease (covid-19) in villages through the APBG, ech village is required to use the revenue and expenditure budget in the field of emergency disaster management and urges the village to refocus activities and budgets to handing covid-19. So that it can be formulated how the village government of krueng dhoue manages the APBG during the pandemic? And how is the strategy of the krueng dhoue village government in preventing the spread of the covid-19 virus outbreak. The research method applied is qualitative, data sourced from primary and secondary with the number of informants 8 people consisting of village officials,trought observation, interviews, and documentation. The results of this study show the APBG management strategi in preventing the covid-19 outbreak, what was done by the krueng dhoue village government was a refocusing of the budget or budget changes that were previously focused, on village development but now they are used to handle the covid-19 outbreak by protecting and distributing the budget. Keywords: Management strategy, APBG, covid-19